Papua New Guinea High Frequency Phone Survey on COVID-19 : Results from Round 1 - World Bank (World Bank, Washington, DC, 2020)
Papua New Guinea (PNG) is the largest country in the Pacific region, and one of the most diverse countries in the world. The key development challenge in this lower-middle income country is how to translate macroeconomic gains from the resource sector into better opportunities and services for PNG’s largely poor and rural populations. The Coronavirus (COVID-19) pandemic has compounded issues for an already weakening economic situation. A strong evidence base is needed to understand the socioeconomic implications of the coronavirus pandemic for Papua New Guinea. Data is needed to inform the policy response to the coronavirus crisis. To monitor and assess the socio-economic impacts of Coronavirus (COVID-19) in Papua New Guinea, five rounds of High Frequency Phone Surveys (HFPS) have been planned and will be conducted quarterly. Data collection began in late June 2020. This report presents the findings from round one and concludes with a policy section to help inform an evidence-based response to Coronavirus (COVID-19) in Papua New Guinea.